Open Heritage: Community-Driven Adaptive Reuse in Europe: Best Practice (Prostor, 2024)
Open Heritage addresses the need for a deeper understanding of the layers and complexities of built cultural heritage, along with the actors and processes involved in its preservation, planning, and reuse. The book presents outcomes from an EU-funded project that examined adaptive reuse cases across Europe, focusing on themes of participative planning, project financing, policies, and governance, thus promoting sustainable, community-driven practices fit for contemporary urban challenges.